The Ukrainian war and the pandemic: the impact on public health and the need for new health digital tools and the next level of intelligence - Geanta , M.; Cucos , B.; Boata , A.; Nuta , A.C.; Nuta , F.M.; Semenov , V.V. (Medicni Perspektivi, 2023)
Against the background of the war in Ukraine, the COVID-19 pandemic has waned from public consciousness as the threat of the virus to health is outweighed by safety concerns during the war. Pandemic restrictions in the European region are being lifted despite low vaccination rates in Central and Eastern European countries and a lack of effective containment strategies. However, Central and Eastern European countries are influenced most by the flow of refugees from neighboring Ukraine where a triple health crisis occurs: an overloaded health system, an ongoing COVID-19 pandemic, and the war. The aim: to review the progress regarding viral surveillance technologies that use genomics, digital, and informational tools, to find the gap in the literature and formulate policy recommendations for continuing surveillance in the context of permacrisis. Unstructured search was conducted through scientific (PubMed and Google Scholar databases) and grey literature using the keywords. The paper highlights aspects of war-related problems of infectious diseases control in Europe, new challenges in healthcare connected with COVID-19 pandemic and war in Ukraine and provides discussion on the role of innovative surveillance systems in tackling infection outbreaks (with COVID-19 pandemic as an example). The paper overviews perspectives of the implementation of the discussed measures. Future COVID-19 outbreaks and new variants are possible. Complex adaptive system models, new tools, and the next level of health and digital intelligence are needed to provide timely and valuable insights. Combining lessons learned from the COVID-19 pandemic, the threat of war, and the need for continuous outbreaks surveillance, new public health and digital intelligence tools must be designed and implemented at regional, European, and global levels.